2019
DOI: 10.1016/j.csbj.2019.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorders and Oxidative Injury: Antioxidant Effects of Zolpidem Therapy disclosed In Silico

Abstract: Zolpidem ( N , N -Dimethyl-2-[6-methyl-2-(4-methylphenyl)imidazo[1,2- a ]pyridin-3-yl]acetamide) is a well-known drug for the treatment of sleeping disorders. Recent literature reports on positive effects of zolpidem therapy on improving renal damage after cisplatin and on reducing akinesia without sleep induction. This has been ascribed to the antioxidant and neuroprotective capacity of this molecule, and tentatively explained according to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 39 publications
2
35
0
Order By: Relevance
“…The most reactive sites are the hydroxyl group and the amine groups. Rather large negative ∆G • HAT values are also computed from the C atoms of the hydrocarbon chain, which is in agreement with the reactivity described for melatonin and zolpidem [38]. In order to verify whether there are more efficient scavenging channels for fluoxetine, we have also investigated the RAF mechanism involving the aromatic C sites.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The most reactive sites are the hydroxyl group and the amine groups. Rather large negative ∆G • HAT values are also computed from the C atoms of the hydrocarbon chain, which is in agreement with the reactivity described for melatonin and zolpidem [38]. In order to verify whether there are more efficient scavenging channels for fluoxetine, we have also investigated the RAF mechanism involving the aromatic C sites.…”
Section: Discussionsupporting
confidence: 77%
“…Sci. 2019, 9, 3631 5 of 15 molecules displaying antioxidant properties, including Trolox [50], melatonin [51], and capsaicin [52], but also psychotropic drugs such as zolpidem [38]. These mechanisms are summarized in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Garcia-Santos et al 43 demonstrated that zolpidem prevented induced lipid peroxidation in rat liver and brain homogenates, showing antioxidant properties similar to melatonin. Bortoli et al 42 investigated in silico the antioxidant potential of zolpidem and identified it as an efficient radical scavenger similar to melatonin and Trolox. Although the mechanisms involved in the pathogenesis and progression of PD are not fully understood, there is overwhelming evidence that oxidative stress plays an important role in dopaminergic neuronal degeneration.…”
Section: Discussionmentioning
confidence: 99%